PENINGKATAN PEMBELAJARAN GERAK DASAR ATLETIK DENGAN PERMAINAN POS BERANGKAI (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine the presence or absence of an increase in learning basic athletic motion with sequential post game at third grade students of SDN 01 Sidosari Kesesi Pekalongan 2014 This study is a Class Action Research (Classrom Action Research), the results of studies using 2 cycles. Each cycle begins with planning, action, observation / evaluation and reflection. As many as 24 students study subjects consisted of 16 boys and 8 female student. Data collection is done by using the data field observations and questionnaires obtained from the evaluation. In a study shows in the first cycle with the value of the percentage of completeness 58% value is less satisfactory. Then resumed on the second cycle with a percentage value 92% value produced in accordance with desired. From the research that has been done can be seen that the post game sequential increase capacity and student learning outcomes in basic athletic motion at third grade students of SDN 01 Sidosari. Improved athletic student learning basic movement using the postal game sequential mastery shown by the percentage value of greater that 92%.